Predictors for Residual Pulmonary Vascular Obstruction after Unprovoked Pulmonary Embolism: Implications for Clinical Practice—The PADIS-PE Trial - Raj, Leela; Robin, Philippe; Le Mao, Raphael; Presles, Emilie; Tromeur, Cécile; Sanchez, Olivier; Pernod, Gilles; Bertoletti, Laurent; Jego, Patrick; Leven, Florent; Lemarié, Catherine A.; Martin, Aurore; Planquette, Benjamin; Le Roux, Pierre-Yves; Salaun, Pierre-Yves; Nonent, Michel; Girard, Philippe; Lacut, Karine; Melac, Solen; Mismetti, Patrick; Laporte, Silvy; Meyer, Guy; Leroyer, Christophe; Couturaud, Francis; for the PADIS-PE Investigators (Thrombosis and Haemostasis, 2019)
Background We aimed to identify risk factors for residual pulmonary vascular obstruction after a first unprovoked pulmonary embolism (PE).Methods Analyses were based on data from the double-blind randomized “PADIS-PE” trial that included 371 patients with a first unprovoked PE initially treated during 6 uninterrupted months; all patients underwent baseline ventilation–perfusion lung scanning at inclusion (i.e., after 6 months of anticoagulation). Each patient's pulmonary vascular obstruction indexes (PVOIs) at PE diagnosis and at inclusion were centrally assessed.Results Among the 371 included patients, residual PVOI was available in 356 patients, and 150 (42.1%) patients had PVOI ≥ 5%. At multivariable analysis, age > 65 years (odds ratio [OR], 2.81, 95% confidence interval [CI], 1.58–5.00), PVOI ≥ 25% at PE diagnosis (OR, 3.53, 95% CI, 1.94–6.41), elevated factor VIII (OR, 3.89, 95% CI, 1.41–10.8), and chronic respiratory disease (OR, 2.18, 95% CI, 1.11–4.26) were independent predictors for residual PVOI ≥ 5%. Patients with ≥ 1 of these factors represented 94.5% (123 patients) of all patients with residual PVOI ≥ 5%.Conclusion Six months after a first unprovoked PE, age > 65 years, PVOI ≥ 25% at PE diagnosis, elevated factor VIII, or chronic respiratory disease were found to be independent predictors for residual pulmonary vascular obstruction.Clinical Trials Registration URL: http://www.controlled-trials.com. Unique identifier: NCT00740883.
Keywords: unprovoked pulmonary embolism; residual pulmonary vascular obstruction; recurrent venous thromboembolism; risk factors